Role of retinoic acid in the stability of the T-helper-type 1 lineage and implications for autoimmunity. (26th February 2015) - Brown, Chrysothemis; Esterhazy, Daria; Sarde, Aurelien; Pullabhatla, Venu; London, Mariya; Arno, Matthew; de Rinaldis, Emanuele; Mucida, Daniel; Lord, Graham; Noelle, Randolph
Abstract: Background: CD4 T cells with features of both T-helper-type 1 (Th1) and 17 (Th17) cells have been implicated in several autoimmune diseases suggesting that plasticity among CD4 T-cell lineages is potentially pathogenic. However, the factors that regulate T-cell lineage stability are largely unknown. Retinoic acid (RA) is synthesised at sites of inflammation. We hypothesised that retinoic acid, a profound epigenetic modifier, could regulate T-cell lineage stability. Methods: We used a mouse model in which retinoic acid signalling is specifically ablated within the T-cell compartment through overexpression of a dominant negative retinoic acid receptor α (RARα) (dnRARα mice) to investigate its role in the regulation of Th1 lineage stability. Genome-wide ChIP-seq analysis was done to identify RARα targets. In parallel, we performed global mapping of regulatory regions, termed enhancers, to gain mechanistic insight into retinoic acid regulation of T-cell fate. The in-vivo relevance of our findings was determined in a model of oral antigen-induced intestinal inflammation. Findings: We found that retinoic acid is crucial for maintenance of the Th1 lineage. Abrogation of retinoic acid signalling in Th1 cells resulted in loss of T-bet expression and STAT4 activity. Th1 cells from dnRARα mice showed enhanced plasticity with the emergence of hybrid Th1–Th17 and Th17 effector cells. Global analysis of RARα binding and enhancer mapping revealed that RA–RARα directly regulated enhancer activity at Th1 lineage defining genes while repressing genes that regulate Th17 cell fate. Retinoic acid inhibition of Th1 plasticity was essential for maintaining appropriate Th cell responses in vivo and preventing autoimmune intestinal inflammation. Interpretation: Our study has identified RA–RARα as a key component of the regulatory network governing maintenance and plasticity of Th1 cells and defines a new pathway for the development of pathogenic Th17 cells. Retinoids might be novel therapeutic agents for Th17-associated autoimmune diseases. Funding: Wellcome Trust.